2019
DOI: 10.1007/s00425-019-03107-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of polysaccharides in dynamic middle lamellae during cotton fibre development

Abstract: This is a repository copy of Metabolism of polysaccharides in dynamic middle lamellae during cotton fibre development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…Based on the profile of extractable callose, we recently estimated the transition from primary to secondary cell wall deposition occurs approximately at 17 DPA ( Guo et al, 2019 ). CDTA-extractable extensins displayed a peak coinciding with onset of secondary wall deposition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the profile of extractable callose, we recently estimated the transition from primary to secondary cell wall deposition occurs approximately at 17 DPA ( Guo et al, 2019 ). CDTA-extractable extensins displayed a peak coinciding with onset of secondary wall deposition.…”
Section: Resultsmentioning
confidence: 99%
“…And 3) the side-chains might be degraded by appropriate hydrolases. Expressed arabinofuranosidase candidates of GH3 and GH51 have been reported and biochemical evidence for arabinofuranosidase activity in crude fibre extracts provided ( Guo et al, 2019 ). The activities were implied in pectic arabinan metabolism, which accompany cotton fibre middle lamella degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the study of pectins in muro has benefited significantly from the application of analyses of mutants associated with pectin biosynthesis ( Francocci et al., 2013 ; Biswal et al., 2018 ; Wang et al., 2019 ), high resolution microscopy using pectin-specific probes ( Ralet et al., 2010 ; Anderson et al., 2012 ; Mravec et al., 2014 ; Mravec et al., 2017a ; Guo et al., 2019 ; Zhao et al., 2019 ), super resolution three-dimensional direct stochastic optical reconstruction microscopy (3D-dSTORM; Haas et al., 2020 ), atomic force microscopy ( Kirby et al., 2008 ; Paniagua et al., 2014 ; Imaizumi et al., 2017 ), and solid state nuclear magnetic resonance spectroscopy ( Wang et al., 2015 ). These studies have shown that the microarchitecture of pectic polysaccharides in the wall is highly complex and modulates during cell expansion, development and in response to external abiotic and biotic stress.…”
Section: Introductionmentioning
confidence: 99%